2012
DOI: 10.1111/j.1600-0501.2012.02454.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing around titanium implants in two rat colitis models

Abstract: The results suggest bone regeneration around implants is not impaired in chemically induced colitis models. Considering that Crohn's disease can affect any part of the gastrointestinal tract including the mouth, our model only partially reflects the clinical situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…In agreement with previous studies based on a rat tibia implantation model, we observed peri‐implant bone formation of titanium screws in the cortical bone. In support of this claim, the medullary bone formation resembles one of previous studies; for example, BV/TV was around 20% (Kuchler et al., 2013 ), only slightly higher than the 10% in the present study. The cortical bone formation was approximately 90% in previous studies (Kuchler et al., 2011 , 2013 ), now also reaching 90% when combining new and old bone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies based on a rat tibia implantation model, we observed peri‐implant bone formation of titanium screws in the cortical bone. In support of this claim, the medullary bone formation resembles one of previous studies; for example, BV/TV was around 20% (Kuchler et al., 2013 ), only slightly higher than the 10% in the present study. The cortical bone formation was approximately 90% in previous studies (Kuchler et al., 2011 , 2013 ), now also reaching 90% when combining new and old bone.…”
Section: Discussionsupporting
confidence: 92%
“…In support of this claim, the medullary bone formation resembles one of previous studies; for example, BV/TV was around 20% (Kuchler et al., 2013 ), only slightly higher than the 10% in the present study. The cortical bone formation was approximately 90% in previous studies (Kuchler et al., 2011 , 2013 ), now also reaching 90% when combining new and old bone. Under these conditions, BDL had not caused a significant and relevant change of the standard parameters of peri‐implant bone formation—the BV/TV and BIC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After treating the images for the histomorphometric analysis, the bone area was quantified concerning the total tissue area of each sample using the same software (Cell Sens Dimensions, Olympus, Tokyo, Japan). The measurements made in this study for analysis were based on the study by Kuchler et al (2013) [ 24 ], as follows: Bone–implant contact (BIC): percentage of the implant surface in direct contact with the bone ( Figure 3 ). …”
Section: Methodsmentioning
confidence: 99%
“…Research into bisphosphonates [ 347 , 355 , 357 , 358 , 359 ] or agonists like selective estrogen receptor modulators [ 347 , 360 ] is typically conducted in the rat as it is an excellent model of osteoporosis. Other diseases, such as arthritis [ 361 ] or Crohn’s disease [ 362 ] and the effects of severe dietary magnesium deficiency on systemic bone density, have been investigated [ 363 ]. Finally, the rat tibia can also be used for mechanical testing, including in dynamic loading models [ 364 , 365 ], as well as for exploring the effects of pulsed ultrasound [ 366 ] or laser therapy [ 367 ].…”
Section: Appendix A1 Research In Non-human Primatesmentioning
confidence: 99%